Diagnostic Possibilities of Optical Coherent Tomography of the Retina during Compression in the Chiasm-Sellar Region - N. A. Gavrilova; E. E. Ioyleva; N. S. Gadzhieva; O. E. Tishchenko; N. Y. Kutrovskaya; A. V. Kuz’mina; A. V. Zinov’eva (Oftalʹmologiâ)
Recovery and preservation of visual functions during compression in the chiasm-sellar region is possible in the case of early diagnosis of pathology and timely surgical decompression. Today optical coherence tomography (OCT) of the retina is one of the most informative methods for diagnosing pathology of the retina and optic nerve. It can, due to the presence of early diagnostic criteria, promptly detect the compression in the chiasm-sellar region and expand the indications for surgical treatment. The literature review presents the results of optical coherent tomography (OCT) of the retina during compression in the chiasm-sellar region. An analysis of literature data revealed that in patients with chiasmatic compression, the thickness of the nerve fiber layer in the peripapillary and macular areas decreases, the thickness of the macular complex, consisting of the retinal ganglion cell layer and the inner plexiform layer, decreases. Also, there is a change in the value of asymmetry between the GCC thickness indices in the nasal and temporal halves of the macular region. It has been established that a decrease in the thickness index of a macular complex may precede changes in the visual field. According to the results of single studies, a correlation was found between the parameters of the peripapillary RNFL thickness and the the internal capillary retinal plexus density in the same areas. The results of literature sources’s analysis are summarized in the table by the parameters studied, the OCT model; etiology, treating methods and the results of the OCT study. Despite the results obtained, the early specific and sensitive OCT diagnostic criteria for chiasmatic compression have not yet been developed. In addition, a change in the thickness of GCC and RNFL can also be observed in the absence of chiasmatic compression in certain types of tumors and in the presence of comorbidities (arterial hypertension). In this regard, it is necessary to conduct further studies that will reveal the informative OСT-diagnostic criteria for compression in the chiasm-sellar region, develop diagnostic algorithms taking into account the type of tumor, the presence of concomitant pathology. Early diagnostic criteria for chiasmatic compression will expand the indications and improve the result of surgical treatment of patients.